Awareness, Practice, and Acceptance of COVID-19 Vaccination among Medical Students from Mansoura University, Egypt: A Cross-sectional Survey - Basant Katamesh; Moustafa Katamesh; W. Abdalrhman; Rawan ElDeeb; Nourhan Hareera; Ahmed Raslan; Ahmed Alabd; Ensanya Abou Neel (Shahrekord University of Medical Sciences, 2022)
Background and aims: The coronavirus disease 2019 (COVID-19) is an emerging transmissible infection that can be prevented by proper hygiene measures and vaccination. With the rise and rapid spread of the Omicron variant, vaccines are currently the best protective measure. This cross-sectional study aimed to assess knowledge, practice, and attitude towards COVID-19 virus and vaccines, particularly Sinopharm, among medical students in Mansoura University, Egypt, from July to September 2021. Methods: A cross-sectional study was conducted using a 35-item questionnaire covering demographic data. COVID-19 knowledge/practice and knowledge/attitude towards vaccines were distributed on medical students' university Facebook group. A score was calculated for knowledge (KS), practice (PS), and attitude (AS). A 60% cutoff was considered satisfactory, and the statistical analysis was carried out using one-way ANOVA, linear regression, and Pearson's coefficient. Results: A total of 837 students participated in this study. The majority (73.12%) of participants showed satisfactory COVID-19 KS and Sinopharm AS (54.77%) but unsatisfactory PS (68.99%) and Sinopharm KS (62.75%). Knowledge had a significant effect on Sinopharm vaccine acceptance. Moreover, females indicated higher COVID-19 KS and PS, whilst males showed higher Sinopharm KS and AS. Gender and year group had a strong correlation with PS. Furthermore, the majority (92.4%) accepted vaccination and believed it should be mandatory (80.41%). The selected vaccines were Pfizer (44.84%) > AstraZeneca (33.86%) > Sinopharm (15.56%) > others. Efficacy, safety, and country of production were the main predictors of vaccine choice. More than half (59.48%) stated that the country in which the vaccine is produced is important when choosing their intended vaccine, and 20.87% stated that their decision is based on vaccine efficacy. Conclusions: COVID-19 was a challenging pandemic; there are several available COVID-19 vaccines, but the most available in Egypt is the Sinopharm vaccine. The results of this study will provide a basis regarding the knowledge and attitude of medical students who play a crucial part in the cycle of infection. These results will help outline the main causes of misunderstandings that can be solved by providing educational needed interventions, implementing protective measures, and distributing scientifically correct data.